KONSEP DEMOKRASI NURCHOLISH MADJID DAN IMPLEMENTASINYA DALAM FILSAFAT PENDIDIKAN ISLAM - Yu’timaalahuyatazaka Yu’timaalahuyatazaka (AT-TAJDID, 2018)
Democracy in Indonesia is being tested. There are several the serious issues which is  highlighted recently such as money politic, political ethics, corrupt, and one of the cases of blasphemy. These problems need to be finished withthe education activities to overcome the nation's problems closely related to the issue of democracy. With the Nurcholish’s concept of democracy, it is hoped to give an awareness that the democracy is the concept of Islam on the Qoran and Sunnah. Besides Islamic education can offer a new theoretical construction of democracy that can provide alternative solutions to the problems of contemporary society in Indonesia. This research uses a library research. The data is obtained by using a literature review. Then, it is understood and analyzed theoritically and philosophically. The result ofresearch is the democratic Islamic education in the idea’s Nurcholish Madjid is Islamic education which prioritizes the principle of togetherness, change and development. Islamic education also needs to instill Indonesian-ness and modernity values in addition to Islam itself.